2007
DOI: 10.1227/01.neu.0000303198.95296.6f
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Effects After Chronic Subthalamic Stimulation and the Topography of the Nucleus in Parkinson's Disease

Abstract: When taking spatial influence into consideration, the neuropsychological effects of chronic STN-DBS were related to a significant anteriorly located active contact within the ventral STN in this preliminary study. This might suggest the existence of topography of STN in patients with Parkinson's disease concerning limbic and associative circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…1,19 In accordance with clinical observations, high-frequency DBS within this region has also been demonstrated to achieve the best motor outcome for patients with PD and avoids the neuropsychological side effects due to current diffusion. 24 Our findings demonstrate significant bursty firing and synchronization of oscillatory cells within the dorsolateral STN, which are similar to those of previous studies. Seifried et al's study not only showed the characteristic firing types of STN cells but also highlighted the importance of various percentages of firing patterns on the delineation of STN topography.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1,19 In accordance with clinical observations, high-frequency DBS within this region has also been demonstrated to achieve the best motor outcome for patients with PD and avoids the neuropsychological side effects due to current diffusion. 24 Our findings demonstrate significant bursty firing and synchronization of oscillatory cells within the dorsolateral STN, which are similar to those of previous studies. Seifried et al's study not only showed the characteristic firing types of STN cells but also highlighted the importance of various percentages of firing patterns on the delineation of STN topography.…”
Section: Discussionsupporting
confidence: 92%
“…24 An acute stimulation test was performed 1 week after surgery to select the optimal stimulation contact and parameters for chronic stimulation.…”
Section: Localization Of Active Contact With Postoperative Ctmentioning
confidence: 99%
“…In our study, we did not perform test stimulation, but no patient suffered post-operative capsular effects because our selection criteria for the trajectory of electrode implantation chose the most appropriate track [54]. The knowledge of STN topography is crucial in general anesthesia DBS surgery; therefore, MER must be used as it is the only intra-operative tool to identify the STN, map its boundaries, and map its sensorimotor component through the detection of movementrelated neuronal firing [61,[63][64][65].…”
Section: General Anesthetic Dbs Proceduresmentioning
confidence: 99%
“…3 A high level of accuracy is required as the motor region of the STN is posterolateral, and unwanted stimulation side effects may occur as a result of direct stimulation or spread to the anteromedial nonmotor area and the adjacent corticospinal tract. 9,18,31,56 Current imaging of STN borders is difficult.…”
mentioning
confidence: 99%